2019
DOI: 10.1177/0960327119836199
|View full text |Cite
|
Sign up to set email alerts
|

Induction of 8-hydroxydeoxyguanosine and ultrastructure alterations by silver nanoparticles attributing to placental transfer in pregnant rats and fetuses

Abstract: A quantitative assessment of the genotoxicity of silver nanoparticles (AgNPs) ascribed to its transplacental transfer and tissue distribution in pregnant rats was carried out in this study. A single intravenous (i.v.) injection of AgNPs with a size range from 4.0 to 17.0 nm was administered to pregnant rats at a dose of 2 mg/kg b.w. on the 19th day of gestation. Five groups beside control, each of the five rats were euthanized after 10 min, 1, 6, 12, or 24 h, respectively. The accumulation of nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 54 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…The protein function is specific to one conformation and an alteration can cause important cell injuries [114]. Both AgNPs and Ag + ions have been shown to interact with proteins, thereby leading to altered conformation, deactivation and even degradation [112,[115][116][117]. When AgNPs bind to proteins, they form corona structures and can express genes involved in DNA damage [112].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein function is specific to one conformation and an alteration can cause important cell injuries [114]. Both AgNPs and Ag + ions have been shown to interact with proteins, thereby leading to altered conformation, deactivation and even degradation [112,[115][116][117]. When AgNPs bind to proteins, they form corona structures and can express genes involved in DNA damage [112].…”
Section: Discussionmentioning
confidence: 99%
“…When AgNPs bind to proteins, they form corona structures and can express genes involved in DNA damage [112]. Ag+ ions released from the AgNPs are bioactive; they have a specific capacity to form complexes with proteins by thiol groups [32,116]. Ag + ions in complexes with proteins can interfere with Na+/Cltransport and contribute to ROS production, disrupt the physiological activity of proteins and even lead to cell death [32,110,116].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional studies on surface composition were included [ 49 , 61 , 90 ]; one showed a reduction in maternal-fetal transfer after chitosan-coating of Ag NPs [ 49 ]. Other studies reported a time-dependent accumulation of Ag NPs, CeO 2 NPs, and fullerenes as they found that the fetal NP concentration increased over time, reached a peak, and then declined [ 54 , 67 , 87 ]. Moreover, critical exposure windows during gestation were evaluated by defining changes in particle transfer after varying the day of NP exposure [ 60 , 61 , 70 , 71 , 87 ].…”
Section: Resultsmentioning
confidence: 99%
“… [ 53 ] Wistar rats 7 Ag NPs/ PVP and [ 110m Ag] 34.9 ± 14.8 b oral/ 1.69 or 2.21 mg/kg/ GD20 g Gamma spectroscopy / Ag NPs identified in fetuses of pregnant rats in amounts significantly exceeding the detection limit. [ 54 ] Wistar rats 30 Ag NPs 4.32 to 16.9 b i.v./ 0 or 2 mg/kg/ GD19 d ICP-OES TEM Time-dependent increase in fetal Ag NP levels, reaching a peak 6 h after injection and showing a decline afterward. [ 55 ] CD-1 mice 16 Au NPs 19.6 or 49.3 a i.v./ 0 or 100 mg/kg/ GD16–17 g ICP-MS AMG Higher amount of Au NPs in maternal livers and placentae from mice injected with 20 nm compared to 50 nm NPs without detectable levels in fetal organs for both sizes.…”
Section: Resultsmentioning
confidence: 99%